Enhancing Speaking Skills Through Role Play and Multimedia Technology - Ridayani, Ridayani; Purwanto, M Bambang (Refleksi: Jurnal Penelitian Tindakan, 2024)
This study explores and evaluates the effectiveness of integrating roleplay methods and multimedia technology in improving students' English-speaking skills in the hospitality industry. Using an action research approach, this study was conducted among third-semester by totalling sampling 30 students majoring in travel business at Prasetiya Mandiri Polytechnic Bogor. This research method includes three cycles of action: planning, action, observation, and reflection. In the planning stage, roleplay scenarios relevant to real situations in the hospitality industry are designed and combined with multimedia technologies such as video tutorials then participate in roleplay activities integrated with these multimedia elements. The results showed that integrating role play and multimedia technology significantly improved students' speaking skills. Students become more confident in using English, can communicate more effectively, and show improvement in pronunciation, intonation, and proper use of vocabulary. This study concludes that the integration of Role play with multimedia technology is a practical approach to improving English-speaking skills among hospitality students.